Experimental Comparative Study on the Use of Photovoltaic Converters for Cooling Photovoltaic Modules - Farkhodjon Turaev; Isroil Yuldoshev; Bozorbek Botirov; Fazliddinov Sadulla (Proceedings of the International Conference on Applied Innovations in IT)
The aim of this research is to study evaporative cooling as an effective method for cooling photovoltaic (PV) modules in the climatic conditions of Uzbekistan. The experiment was conducted during the summer period at the heliopolytechnic site of Tashkent State Technical University named after Islam Karimov. Among various cooling options for modules, evaporative cooling was selected as the most cost-effective and technologically simple solution for manufacturing and use. The principle of evaporative cooling of a wet object is based on heating and evaporating moisture using the heat of the cooled object. According to researchers, at an ambient temperature of 35-45°C, the maximum temperature of a photovoltaic module without cooling reached 66.1°C. The maximum temperature of the photovoltaic module with evaporative cooling was 46.8°C. Without cooling, the module's temperature would have reached 66.1°C. The reduction of the module temperature by 33°C demonstrates the effectiveness of evaporative cooling. Two photovoltaic panels with a power output of 290 W were used for the experiment. The difference in average electrical power between the uncooled PV module and the PV module with evaporative cooling was 23 W/h. The results indicate that evaporative cooling is indeed effective and can significantly reduce the power loss of PV modules due to overheating.